ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI KELAPA DALAM (Cocos nucifera Linn) PADA LAHAN GAMBUT DAN LAHAN MINERAL DI KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Khairizal; Sisca Vaulina; Hajry Arief Wahyudy (DINAMIKA PERTANIAN, 2018)
ABSTRACT In Indragiri Hilir Regency, coconut grows on peat land and mineral land. The difference in land conditions will affect the amount of production and income that farmers will receive. The objectives of this study are: (1) To determine the characteristics of Deep Coconut farmers on peat land and mineral land in Indragiri Hilir Regency. (2) Analyzing the production and income of Deep Coconut farmers on peat land and mineral land in Indragiri Hilir Regency. (3) Analyzing what factors influence the production of Deep Coconut on peat land and mineral land in Indragiri Hilir Regency. This study uses a survey method. The research location was determined in Kempas District for peat land and Concong District for mineral land. The sample is determined by purposive sampling, which is based on the age of coconut plants with a range of 10-15 years. Data were analyzed descriptively qualitatively and quantitatively, using the Cobb-Douglas production function. The results of the study show that (1) peat land and mineral land farmers have relatively the same characteristics farmers, the age of productive farmers, average education level graduating from elementary school, number of family dependents 3-4 people and having experience in farming for 20-29 years. (2) Coconut production on peat land is greater than mineral land, as well as income. (3) Factors that significantly affect coconut production on peat land are land and the number of productive plants, while for mineral land, they are processed. Keywords: Coconut, Peat Land, Mineral land, Cobb-Douglas